Hydrological Simulation and Prediction of Typical Tributaries in Songhua River Basin Based on CMIP6 Climate Scenarios: A Case Study of Ant River Basin - GONG Xiao; DAI Changlei; LI Shuling; LI Chunshuang (Renmin Zhujiang)
Assessing the impacts of future climate change on runoff processes in the Ant River Basin can provide a scientific basis for regional water resource management and disaster prevention and mitigation. The SWAT model was constructed based on the hydrometeorological data of the Ant River Basin from 1971 to 2021, and the model was driven by data from three scenarios of 11 climate models in CMIP6 to analyze the characteristics of runoff evolution in the Ant River Basin under future (2020–2100) climate change. The results showed that ① the coefficient of determination (R2) and the Nash coefficient (ENS) for the regular and validation periods of the monthly runoff rate at Lotus (II) Hydrological Station in the Ant River Basin are both greater than 0.7, and the percentage of bias (PBIAS) is less than ±5; the SWAT model is fully used in this basin. ② The maximum and minimum temperatures in the Ant River Basin in the future show an increasing trend, with average annual growth rates of 0.036, 0.039, and 0.05 °C/a for the maximum temperature and 0.046, 0.05, and 0.061 °C/a for the minimum temperature under the three emission scenarios, respectively; the precipitation shows an increasing trend, with growth rates of 1.146, 1.16, and 1.26 mm/a, respectively, and the evapotranspiration shows a non-significant decrease under the SSP1-2.6 scenario and a significant increase under the SSP2-4.5 and SSP5-8.5 scenarios, with growth rates of 0.992 and 1.756 mm/a, respectively. ③ The weighted multi-model ensemble approach can effectively improve the simulation accuracy and reduce the uncertainty of a single climate model. ④ The runoff in the Ant River Basin increases significantly under SSP1-2.6 scenario, with a rate of change of 0.309 m3/(a·s); it decreases significantly under SSP2-4.5 scenario, with a rate of change of -0.044 m3/(a·s) and increases non-significantly under SSP5-8.5 scenario, with a rate of change of 0.034 m3/(a·s).